Preliminaries for a new mathematical framework for modelling tumour growth using stress state decomposition technique - Di Rado, Héctor Ariel (2020)
Fil: Di Rado, Héctor Ariel. Universidad Nacional del Nordeste. Facultad de Ingeniería; Argentina.